Lutas por moradia na cidade de Diadema (1983-1996): cooptação política e acomodação de conflitos do capital - Santos, Joana Darc Virgínia dos (2009)
This study aimed to examine the struggle for housing in the city of Diadema related to local authorities in the period 1983 to 1996, in which the Worker's Party (PT) had governmental hegemony. Such struggles, specifically in the case of Diadema, were articulated by people who, due to the difficulty to access their demands, organized themselves, meetings at various points of the city, like garages, sidewalks and bars, where they talked about possible solutions to meet their basic needs for survival, among them the realization of housing rights. Some of these groups were nested in channels of popular participation established by the government of the PT in the City Hall of Diadema and they were the first experience of covenant between the government and organized segments of the population, that resulted in an urbanization project called Sanko. The entities that benefited from this closeness were: Eastern United Association of Struggle for Housing in, Taboão Homeless Association, Our Land Our Fight Association, Association of Officials in the Struggle for Housing and Almiro Senna Ramos. Based on an extensive documentation consisted of minutes of meetings and official documents of the City Hall (found in the association Our Fight Our Land Association and the Department of Housing of Diadema), testimonies of activists of some associations and newspaper articles, it was chosen to objectify, from the internal logic contained in the relations between the government and civil society, the expression of a particular way of being of the State, in its local dimension. In order to conduct this study and with the objective of recovering the internal logic of the social dynamics resulting from the correlation of forces within the movement and the government the analysis of immanence was used. From this analysis it was possible to obtain some conclusion son the effectiveness of popular participation in the city of Diadema. It was noted that the mechanisms that enabled the implementation of the Master Plan in that city in 1994 emerged from this dynamic, in which local landowners were also involved, as it appears on the cooptation of co-partisan political activists in those associations by political parties